Planeamento Operacional de Curto Prazo de Sistemas de Energia Hidroeléctricos - Catalão, João Paulo da Silva (2010)
Made available in DSpace on 2010-04-28T10:07:21Z (GMT). No. of bitstreams: 1 MSc_JPSCatalao.pdf: 1511043 bytes, checksum: 4b8b804107248ca15e22fe216760c2c5 (MD5) Previous issue date: 2003